ประสิทธิผลของรูปแบบการดูแลผู้ป่วยโรคไตเรื้อรังโดยใช้การจัดการโรคเชิงบูรณาการและ การจัดการรายกรณีในหน่วยบริการปฐมภูมิ ภาคตะวันออกเฉียงเหนือ Effectiveness of Care Model for Chronic Kidney Disease Patients Using Integrated Disease Management and Case Management in Primary Care Units, Northeast - แก่นการ วราทิพย์; ดำนอก เกษม; อนุตระกูลชัย ศิริรัตน์ (วารสารการพยาบาลและการดูแลสุขภาพ, 2019)
Chronic kidney disease (CKD) is a global health burden with a high economic cost to health systems. The principles of chronic care model using integrated disease management and case management concepts can delay CKD progression. The randomized controlled trial research aims to study the effects of care model for chronic kidney disease patients using integrated disease management and case management in primary care units, Northeast of Thailand. The participants consisted of 200 patients with chronic kidney disease, randomly allocated into two groups of an experimental and a control group. The experimental group received participatory care, practice self-management skills to slow CKD progression, coordination of multidisciplinary care teams by nurse case managers. The control group received standard care from the Tambon Health Promotion Hospital. Data were collected between March 2018 and February 2019. Evaluating clinical outcomes were self-management behavior to slow CKD progression and the quality of life measure. Data analyzed with descriptive statistics and independent t- test. Most of participants were female, an average age of 63 years, and the comorbidities were diabetes mellitus with hypertension. The experimental group had the absolute eGFR (55.71 versus 50.68 ml./min/1.73 m2), self-management behavior mean scores and quality of life at the end of the study increased more than the control group with statistical significance. Mean blood pressure level (133.11 / 81.59 versus 136.45 / 84.06 mmHg) and HbA1c were significantly lower than the control group at the level of .05. The average body mass index and the waist line of the experimental group and the control group were not different. Care model for chronic kidney disease patients using integrated disease management and case management can delay CKD progression in primary care units.